The impact of knowledge sharing through social media among academia - Ghazali, Saadiah; Sulaiman, Nor Intan Saniah; Zabidi, Nerda Zura; Omar, Mohd Faizal; Alias, Rose Alinda (2016)
The world of research require researcher, academia and lecturers to share knowledge among them. With the invention of social media, knowledge sharing process has been more effective and easy. Previously, there were numerous researches done to investigate the effect of social media utilization for public used.There were also study that aimed to study social media effects in educatioanal sector but those study were centered around student’s perspective.Less consideration is given towards academia’s perspective. Therefore, this study is directed to explore other niche area on knowledge sharing environment where it will focused on the effects of social media on knowledge sharing among academia.Initially, literature review analysis was done to discover the potential factors that encourage academia to engage in social media.Ability to facilitate communication, idea generation and group establishment are the most cited reasons. Not only that, this paper will highlight the significance of performing this study.In conclusion, there is no doubt that social media do enhance and upgrading the knowledge sharing process thus assisting academia in their scholarly work.